Dinâmica climática e comportamento térmico em distintas local climate zones em uma cidade tropical costeira - Pereira, Camila Tavares (Universidade Federal de São Carlos, 2020)
In recent decades, recognizing the harmful effects of urbanization on human health, numerous studies have been carried out in tropical and subtropical cities, mainly regarding Urban Heat Islands (UHI) and thermal comfort. In addition, advances in the field of applied urban climatology were made using the methodology developed by Stewart and Oke (2012), based on the classification of the environment in Local Climate Zones (LCZ). In this perspective, this thesis aimed to evaluate the dynamics and thermal behavior that different LCZs, conditioned by physical, social, and economic aspects, have on the formation and alteration of the microclimate in the city of Santos (São Paulo). For this, several methods and tools were adopted in order to produce relevant information about the city's climate. In this way, three main approaches were analyzed and discussed on the present thesis: the UHI seasonality in LCZs; the influence of different urban spaces on the surface and mean radiant temperature; and thermal comfort in different LCZs. The seasonal variability of the UHI was analyzed based on the collection of climatic data during summer and winter under "ideal weather conditions". The results showed two thermal behaviors distinct from the UHI in the LCZs. During the night time, maximum UHI values were observed in the compact high-rise building (HRB), while in the daytime, higher UHI magnitudes were observed in the compact low-rise (CLR2), both showing the influence of the sky view factor and vegetation in the UHI. Regarding the second approach, in order to observe the influence of urban morphologies on the mean radiant temperature and on the surface temperature, two methodologies were used: calculation of the surface temperature and simulations of the urban model. The first was obtained through the Land Surface Temperature plugin (QGIS - v2.8.9), and the second from The Solar LongWave Environmental Irrandiance Geometry model (SOLWEIG, v2019a - QGIS). In both analyzes, the contribution of vegetation and the shading of buildings were evident in the reduction of the mean radiant temperature and in the surface temperature. In the third approach, HRB and CLR2 were chosen for the analysis of thermal comfort, using the Physiological Equivalent Temperature (PET), calculated through SOLWEIG. Thus, the socio-spatial distinction of LCZs formed from the valuation of spaces was evident, mainly due to the tourism market, which influences the urban infrastructure available in each area until today. These spaces were decisive for the levels of thermal comfort observed during summer and winter in the two LCZs. Thus, the results showed the critical situation of thermal stress of CLR2 citizens, especially during the summer. In such a way, the thesis advanced both in the theoretical enrichment of the urban climate of a tropical coastal city and in the question of planning, when discussing the variables that may contribute to the environmental quality of each LCZ.
Climate dynamics and thermal behavior in different local climate zones in a tropical coastal city
Keywords: Ilhas de calor urbano; SOLWEIG; Temperatura radiante média; Temperatura de Superfície; Conforto térmico; Santos; Local climate zones; Urban heat island; Mean radiant temperature; Land surface temperature; Thermal comfort; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::CLIMATOLOGIA GEOGRAFICA